Efficiency Justification of the Special Tread Wheelset Passage Along Specific Track Section - Hauser, VladimÃr; Gerlici, Juraj; Nozhenko, Olena; Kravchenko, Kateryna; LoulovÃ¡, MÃ¡ria (International Journal of Engineering and Technology, 2018)
In urban railway environments, the problem of tramcars passing small radius arches appears to be topical. In this regard is proposed that the wheelsets should be complemented on the outer side of the wheels with a second tread of a lower radius, intended exclusively for ride in arches of the track with a radius which the conventional wheelsets cannot even theoretically pass without creep. The complemented wheel tread enters into operation (or out of action) as a result of passing over a specially shaped rail located in the intersections before and behind the small radius arc. In this process, there is a step change in the wheel-rail contact location - similar to what is commonly used when riding on a facing rail located in the immediate vicinity of the point frog. The paper deals with the comparison of these two cases based on a simulation analysis of vehicle ride. The contact point change is evaluated by steering forces, angles of attack and the creep velocities. Four times longer service life of the proposed shaped rail than the one of a frog point is expected. Â Â